Development of fermented sea buckthorn (Hippophae rhamnoides L.) juice and investigation of its antioxidant and antimicrobial activity - Liu, Xiaolu; Lv, Mingshan; Maimaitiyiming, Ruxianguli; Chen, Keping; Tuerhong, Nuersiman; Yang, Jiangyong; Aihaiti, Aihemaitijiang; Wang, Liang (Frontiers in Nutrition, 2023)
Sea buckthorn (Hippophae rhamnoides L.) is an edible and medicinal plant species. However, due to its sour taste, it is not readily accepted by consumers. To overcome this, fermentation can be used to change its flavor profile. In this study, we used response surface methodology (RSM) to determine the best process for producing fermented sea buckthorn juice (FSBJ) using probiotics. The biological enzyme activity and total flavonoid content (TFC) of sea buckthorn juice (SBJ) increased after fermentation. When the number of bacteria inoculated was 4.08 × 106 CFU/mL and the inoculation ratio was 30% Z. mobilis, 5% L. casei, 13.75% L. plantarum, 31.25% P. acidilactici, 12.5% L. animalis, and 7.5% P. pentosaceus, the amount of sugar was 2.98% (w/v) after 20 h of fermentation at 37°C, and the superoxide dismutase (SOD) activity reached 725.44 U/mL, and the TFC reached 2.38 mg/mL. FSBJ demonstrated strong antimicrobial activity against Escherichia coli, Staphylococcus aureus and Botrytis cinerea. Then, to investigate the antioxidant capacity of FSBJ, we used H2O2 to induce oxidative stress in C2C12 cells and assessed the protection conferred by FSBJ to damaged cells. It was discovered that after 24 h of treatment with FSBJ, not only was there an increase in the activities of intracellular SOD and glutathione peroxidase (GSH-Px), but also a reduction in reactive oxygen species (ROS) content, catalase (CAT) activity, and malondialdehyde (MDA) content. This research lays the theoretical groundwork and provides reference materials for the improved fermentation of sea buckthorn and demonstrates its resulting antioxidant effect.